2018
DOI: 10.1002/2017jd027703
|View full text |Cite
|
Sign up to set email alerts
|

Cyclone Activity in the Arctic From an Ensemble of Regional Climate Models (Arctic CORDEX)

Abstract: The ability of state‐of‐the‐art regional climate models to simulate cyclone activity in the Arctic is assessed based on an ensemble of 13 simulations from 11 models from the Arctic‐CORDEX initiative. Some models employ large‐scale spectral nudging techniques. Cyclone characteristics simulated by the ensemble are compared with the results forced by four reanalyses (ERA‐Interim, National Centers for Environmental Prediction‐Climate Forecast System Reanalysis, National Aeronautics and Space Administration‐Modern‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 85 publications
7
27
0
Order By: Relevance
“…They showed that the ASRv1, during winter, detects 28% more cyclones than ERA-I. A similar result was shown in Akperov et al, (2018), where it was found that ASRv2 resolves more small and shallow cyclones. Compared to the Noer et al (2011) PL climatology, ASRv1 was able to resolve 89% of the PLs compared to 48% resolved in the ERA-I.…”
Section: Asrsupporting
confidence: 65%
“…They showed that the ASRv1, during winter, detects 28% more cyclones than ERA-I. A similar result was shown in Akperov et al, (2018), where it was found that ASRv2 resolves more small and shallow cyclones. Compared to the Noer et al (2011) PL climatology, ASRv1 was able to resolve 89% of the PLs compared to 48% resolved in the ERA-I.…”
Section: Asrsupporting
confidence: 65%
“…The pattern correlation coefficients between the fields from ERA‐Interim and the model simulations are larger than 0.87. Obviously, in August, the model underestimates the SLP interannual variability in the northern Barents/Kara Sea, which is associated with underestimated cyclone frequency and depth (Akperov et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…For modeling SIC changes, RCM data provided by the Coordinated Regional Downscaling Experiment (CORDEX) was used. The Arctic CORDEX initiative is an international coordinated framework to produce an improved ensemble of regional climate change projections as the input for impact and adaptation studies aimed at a better understanding of the regional climate in the Arctic [22]. The RCM is based on dynamic downscaling of the GCM, enabling more detailed forecasting in specific regions with improved spatial resolution.…”
Section: Climate Datamentioning
confidence: 99%